Last-mile logistics innovations : the balance between customer demands and sustainability - Pangrazzi, Giovanni; Kolář, Petr; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Over recent years, the significant growth in e-commerce has put a lot of pressure on last-mile logistics, which has to face increasingly complex situations. Customers are becoming more demanding; they ask for shorter delivery times and are willing to pay a very low price for it. The consequences for last-mile logistics are higher costs and a lack of efficiency in many operations. At the same time, a sense of responsibility toward environmental issues is growing among customers, who ask companies to be more sustainable. The problem is that sustainability for companies translates into an increase in costs. The goals of the thesis are several. First, identify the main issues of the last-mile logistics. Then, indagate what innovations have been implemented in the sector or are considered for the future and whether they have positive effects on cost and sustainability. Finally, find out whether there will be a balance in the future between sustainability and customer satisfaction, remaining cost-efficient. The methodologies consist of a theoretical and a practical part. In the first part, a systematic literature review was made to create an academic background on the mentioned topics. The second part consists of qualitative research based on interviews with experts. The data collected have been analyzed and discussed with those of the theory to see if they support, complete, or question them. The results of this thesis emerge a more precise and complete picture of the last-mile logistics and its issues; some innovations considered relevant for the industry’s future; the reasons behind the introduction or not of sustainable innovations. Finally, customers and governments seem to be the central elements on which will depend the future of the last mile, to ensure sustainability and demand satisfaction.
Vedoucí práce: Petr Kolář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses